DIGITAL LITERACY: UNDERSTANDING NORMS AND ETHICS IN THE ONLINE REALM - Abdul Rozak; Karman Karman (ADISAM Publisher, 2025)
This research discusses the importance of digital literacy in understanding and applying norms and ethics online. With the increasing use of digital technology, the ability to access, evaluate and use information effectively has become crucial. Digital literacy involves not only technical skills but also ethical understanding and the ability to interact sensibly in digital spaces. This study highlights the role of digital literacy education and training as a tool to empower individuals to face the challenges of misinformation and unethical behaviour. Through this approach, collective efforts are expected to create a safer and more productive online environment, in line with social norms and global policy values. This research recommends collaboration between governments, educational institutions and non-profit organisations to strengthen people's digital literacy competencies.